Theatre-making in the age of #MeToo: Working cross-culturally toward a framework for making safer creative spaces - Park, Younghee (Université de technologie du Queensland, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Plan de lutte contre les violences et le harcèlement sexistes et sexuels dans le spectacle vivant - Ministère de la Culture français (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

The Royal Court in the Wake of #MeToo - Fallow, Catriona; Mullan, Sarah Jane (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Encouraging Safer and More Supportive Working Practices in Theatre - Society of London Theatre; UK Theatre (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Education in Theatrical Intimacy as Ethical Practice for University Theatre - Shawyer, Susanne; Shively, Kim (Journal of Dramatic Theory and Criticism, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël; acting; ethics; pedagogy; theatre; theatrical intimacy

Masculinity after #MeToo in Mainstream Theatre - Mignon, Eloïse; Rae, Paul (Performance Research, 2019)
Keywords: #MeToo; Arthur Miller; Bibliographie; Geoffrey Rush; King Lear; Nettoyer; Raphaël; Sarah Kane; masculinity; theatre

Supporting Brave Spaces for Theatre-​Makers Post-#MeToo: A Chicago-Based Study on Rehearsing and Performing Intimacy in Theatre - Studham, Susan Fenty (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Krytyczki as Activists: On Theatre Criticism, Affect, Objectivism and #MeToo in Polish Drama Schools: Interview with Monika Kwaśniewska - Lech, Kasia (Critical Stages/Scènes critiques, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

We Get It: Calling Out Sexism and Harassment in Australia’s Live Performance Industry - Thomasson, Sarah (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Performing Arts Training in the Age of #MeToo - Spencer, Jennifer (Voice and Speech Review, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

The Change You Want to See: Results of the first-ever survey of workplace sexual harassment in the Canadian performing arts, film, and television industries - Aftermetoo (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Analysis of the “Regional Survey on Violence and Harassment in the Workplace in the Audiovisual and Performing Arts Industry in Latin America” - FIA-LA; UNI Americas MEI (International Federation of Actors et UNI Americas MEI / Panartes, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

#MeToo: Theatre Women Share Their Stories - Heyliger, Yvette (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Institutional Responses to #MeToo: A Conversation - Mengesha, Weyni; Dreyer-Lude, Melanie; Clarke, Kristian; Shaw, Kathryn; Warwick, Jacqueline; Palmer, Alisa; Dubois, Frédéric (Canadian Theatre Review, 2019)
Theatre administrators, artistic directors, and heads of programs from across Canada have a conversation about how institutional policies and cultures have shifted in the wake of #MeToo. The conversation features Kristian Clarke, Executive Director of the Dancer Transition Resource Centre (DTRC); Frédéric Dubois, Director of the French Section, National Theatre School; Melanie Dreyer-Lude, Chair of the Department of Drama at the University of Alberta; Weyni Mengesha, Artistic Director of Soulpepper Theatre; Alisa Palmer, Artistic Director of the English Section, National Theatre School; Kathryn Shaw, Artistic Director of Studio 58 at Langara College; and Jacqueline Warwick, Director of the Fountain School of Performing Arts, Dalhousie University. The participants reflect on the challenges of taking stock of the impacts and effects of a cultural movement that is still unfolding and the ways in which #MeToo has changed the relationship between training institutions and the performing arts industry.
Keywords: #MeToo; Bibliographie; Nettoyer; Raphaël; intimacy coaching; performing arts industry; sexual harassment policy; theatre training

“Sorry Not Sorry”: Apologizing in the Wake of #MeToo - MacArthur, Michelle (Canadian Theatre Review, 2019)
This article explores what it means to apologize for misconduct in the #MeToo era through three examples from the Canadian theatre industry: a private apology (Randolph College for the Performing Arts), a public apology (Citadel Theatre), and an absent apology (Soulpepper Theatre). Understanding a public apology as a performative utterance meant to restore a community’s trust, this article suggests the importance of examining the paratexts generated by and around it that help it achieve its function. From policy revisions, to media interviews, to public forums, these materials and events are crucial in the meaning-making process in which a #MeToo apology is engaged, especially when the theatre community’s access to the apology itself is limited. The article concludes by situating its case studies in relation to issues of misconduct in theatre education and training institutions.
Keywords: #MeToo; #SorryNotSorry; Bibliographie; Canadian theatre; Citadel Theatre; Nettoyer; Randolph College for the Performing Arts; Raphaël; Soulpepper Theatre; public apologies

A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël

Mapping the Stage Differently: Theatre #MeToo Movement and Internet Culture in South Korea - Yoon, Soo Ryon (Gender IT : Feminist reflexion on Internet policie, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Creating Space for Gender Diverse Theatre - Meredith, John; Levine, Sloth; Gender Explosion Working Group (StageSource, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Keywords: Bibliographie; Nettoyer; Raphaël

Preventing Sexual Harassment and Abuses of Power: A Code of Behaviour - Royal Court Theatre (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

The power of abuse - Harvie, Jen (The Routledge Companion to Theatre and Politics, 2019)
Following revelations about sexual abuse in theatre and other entertainment industries in autumn 2017, this chapter explores the conditions which allow or
Keywords: Bibliographie; Nettoyer; Raphaël

Line Drawn Summit and Survey Report - Stone, Meg (Impact, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Sexual Harassment, Criminal Misconduct & Bullying in Australian Live Performance - Media Entertainment Arts Alliance (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Facing (and Fixing) the Problem of Sexual Harassment in Theatre - Lehman, Stefanie Maiya; Morris, Celestine (Southern Theatre, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Harassment and bullying in the theatre industry: a report - The Stage (The Stage, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Considering Queerness - Actor Training's Issues and Alternatives - LeBlanc, Jacob G. (Université du Commonwealth de Virginie, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

"for People Who Aren't Sure Who They Are, Theatre is a Great Place to Be": Narratives of Actors and their Sexual Identities - McCadden, Theodore Edward (Pennsylvania State University, 2015)
Keywords: Bibliographie; Nettoyer; Raphaël

Examining the Embodied Learning Experiences about Gender in Gay and Bisexual Male Actors - McCadden, Ted; Wright, Robin Redmon (Adult Education Research Conference, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Don't Act, Don't Tell: Discrimination Based on Gender Nonconformity in the Entertainment Industry and the Clinical Setting - O’Connell, Mark (Journal of Gay & Lesbian Mental Health, 2012)
The author describes anti-homosexual attitudes in the entertainment industry. Effeminate male actors generally have a hard time being cast, whether for gay or straight roles. Attitudes in the performing arts mirror those in society as a whole. Case reports are interspersed in the discussion to illustrate the points.
Keywords: Bibliographie; Nettoyer; Raphaël; acting; anti-gay; discrimination; gender nonconformity; homophobia; performing arts

Sexual Orientation & Gender Identity Diversity in Entertainment: Experiences & Perspectives of SAG-AFTRA Members - Badgett, M.V. Lee; Herman, Jody L. (SAG-AFTRA et The Williams Institute, 2013)
Keywords: Bibliographie; Nettoyer; Raphaël

Gay men in the performing arts: Performing sexualities within ‘gay-friendly’ work contexts - Rumens, Nick; Broomfield, John (Organization, 2014)
Building on emerging research on ‘gay-friendly’ organizations, this article examines if and how work contexts understood and experienced as ‘gay-friendly’ can be characterized as exhibiting a serious breakdown in heteronormativity. Taking the performing arts as a research setting, one that is often stereotyped as ‘gay-friendly’, and drawing on in-depth interview data with 20 gay male performers in the UK, this article examines how everyday activities and encounters involving drama school educators, casters and peers are shaped by heteronormative standards of gay male sexuality. Adopting a queer theory perspective and connecting with an emergent queer theory literature in organization studies, one concern articulated in this article is that heteronormative constructions of gay male sexualities constrain participants’ access to work; suggesting limits to the abilities and roles gay men possess and are able to play. Another concern is that when gay male sexualities become normalized in performing work contexts, they reinforce organizational heteronormativity and the heterosexual/homosexual binary upon which it relies. This study contributes towards theorizing the heteronormative dynamics of ‘gay-friendly’ places of work, arguing that gay male sexualities are performatively instituted according to localized heteronormativities which reinforce contextually contingent, restrictive heteronormative standards of gay male sexuality which performers are encouraged to embody and perform both professionally and personally.
Keywords: Bibliographie; Nettoyer; Raphaël

Irish Equity Survey 2016 - Irish Equity (2016)
Keywords: Bibliographie; Nettoyer; Raphaël

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching

#MeToo In Polish Theatre Education - Kwaśniewska-Mikuła, Monika (Philosophy, Sociology, Psychology and History, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

An Examination on Sexual Harassment Activities in the South African Professional Performing Arts Industry - Yende, Sakhiseni Joseph (Journal of African Films & Diaspora Studies, 2021)
Keywords: Bibliographie; Nettoyer; Patriarchal power; Performing arts industry; Professional theatres; Raphaël; Sexual harassment; Women in theatre

Sexual Harassment in the Norwegian Theatre World - Kleppe, Bård; Røyseng, Sigrid (The Journal of Arts Management, Law, and Society, 2016)
The aim of this article is to provide insight into the phenomenon of sexual harassment in the theatre world. A survey among Norwegian actors is presented showing that sexual harassment is much more prevalent in the theatre world than in Norwegian work life in general. Further, the article aims at understanding why the prevalence is as high as it is. Based on qualitative interviews, the article points out some risk factors that shed light on the high prevalence of sexual harassment. Lastly, the risk factors are related to charismatic authority as an important power base in the theatre world.
Keywords: Art organizations; Bibliographie; Nettoyer; Raphaël; charismatic authority; gender roles; mixed methods; sexual harassment; theatre